2000
DOI: 10.1086/315761
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology ofStreptococcus pneumoniaeCausing Invasive Disease in 5 Countries

Abstract: A multicenter study was done during 1993-1995 to investigate prospectively the influence of several prognostic factors for predicting the risk of death among patients with pneumococcal bacteremia. Five centers located in Canada, the United Kingdom, Spain, Sweden, and the United States participated. Clinical parameters were correlated to antibiotic susceptibility and serotyping of the 354 invasive pneumococcal isolates collected and to molecular typing of 173 isolates belonging to the 5 most common serotypes (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 35 publications
6
67
1
1
Order By: Relevance
“…Data collected over a 2-year period (1984 and 1985) from a South African hospital in Gauteng Province in South Africa showed that serotype 3 caused higher case fatality ratios than other serotypes (10). High mortality rates have also been observed in serotype 3 cases from other countries, including Spain and the United States (14). We found high case fatality ratios in this population dominated by HIV-infected individuals, with no difference between serotype 3 compared with non-serotype 3 cases.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Data collected over a 2-year period (1984 and 1985) from a South African hospital in Gauteng Province in South Africa showed that serotype 3 caused higher case fatality ratios than other serotypes (10). High mortality rates have also been observed in serotype 3 cases from other countries, including Spain and the United States (14). We found high case fatality ratios in this population dominated by HIV-infected individuals, with no difference between serotype 3 compared with non-serotype 3 cases.…”
Section: Discussionsupporting
confidence: 54%
“…Pneumococci with serotype 3 capsules are associated with invasive pneumococcal disease (IPD) in older children and adults (13,14). Serotype 3 pneumococci have been associated with higher case fatality ratios compared to other serotypes (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some capsular serotypes have been shown to cause more severe and lethal disease than others (12). Mortality rates from invasive disease were increased with serotypes 3, 5, and 23, while infections with serotypes 1, 4, 6, 9V, 12F, and 14 were associated with lower mortality rates (3,31,34,46). Furthermore, during experimental pneumococcal meningitis serotypes 3 and 23 caused more severe inflammation than serotypes 1, 5, 9, and 7F (26,67).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the actual dimension of the link between transmissibility and resistance may be difficult to evaluate without extensive studies on the population biology of microbes associated with humans. Although the epidemiology of nonvirulent and nonresistant organisms remains to be evaluated, some important observations (163) indicate that in countries such as Sweden, where antibiotic-mediated selection is low, epidemics of antibioticsusceptible but pathogenic bacteria may be, as in the preantibiotic era, the usual case. Studies of commensal bacteria in wild animals also suggest that the gut flora of wild populations with little human contact (and thus no contact with antibiotics) shows very low levels of antibiotic resistance (288), whereas those from the guts of animals that have been in contact with humans show higher levels of antibiotic resistance (143,144).…”
Section: Are Antibiotic-resistant Bacteria More or Less Epidemic?mentioning
confidence: 99%